The Constitutional Right to Bargain Collectively: The Ironies of Labour History in the Supreme Court of Canada - Tucker, Eric (Labour / Le Travail, 2008)
The article focuses on the constitutional right to bargain collectively in Canada. Employers in Canada have adopted labour management policies that including resistance to and avoidance of collective bargaining, shifting from secure employment forms and increasing demand on the workforce. It mentions the Hospital Employees' Union (HEU) which had successfully fought a long battle to achieve pay equity for its largely female membership.
Keywords: Canada; Collective bargaining; Collective labor agreements; Employers; HOSPITAL personnel -- Salaries, etc.; Labor Unions